The Two Transitions in Central and Eastern Europe and the Relation between Path Dependent and Politically Implemented Institutional Change - Joachim Zweynert; Nils Goldschmidt (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2005)
The increasing gap between the formerly socialist countries of Central and Eastern Europe (CE & EE) with regard to both their economic and political performance cannot be explained by their different starting conditions after the breakdown of the Soviet Union alone. Rather, it is due to cultural and historical circumstances that shape the particular tradition and societal environment. Taking a cultural approach and referring to the newer literature on the transfer of institutions, we try to improve the understanding of the interrelation between formal and informal institutions. Our central thesis is that the "reaction rate" of informal institutions depends on their compatibility with imported formal institutions. The transition processes in CE & EE can tell us much about the relation between path dependent and politically implemented institutional change. During the 20th century the countries of CE & EE twice went through rapid institutional change: For centuries they had acculturated to Western Europe, but as a result of the October Revolution "Eastern" patterns were imposed upon them. Since the breakdown of the SU in the late 1980s they have "returned to Europe" by (re-)establishing democracy and capitalism. In our opinion, to understand the differences in performance between the transition countries, it is necessary to interpret both transitions as processes of institutional transplantation and ask how the informal institutional settings in the different countries interacted with the imported formal institutions.
Keywords: P51; Z10; 330; Cultural Economics; Institutions; Transition; Path Dependence; Übergangswirtschaft; Institutioneller Wandel; Pfadabhängigkeit; Evolutionsökonomik; Osteuropa